2021
DOI: 10.1101/2021.02.26.21252501
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The impact of varying class sizes on epidemic spread in a university population

Abstract: A common non-pharmaceutical intervention (NPI) during the Covid-19 pandemic has been group size limits. Further, educational settings of schools and universities have either fully closed or reduced their class sizes. As countries begin to reopen classrooms, a key question will be how large classes can be while still preventing local outbreaks of disease. Here we develop and analyse a simple, stochastic epidemiological model where individuals (considered as students) live in fixed households and are assigned to… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The estimated breakdown of RS revealed a number of notable patterns. As the number of classes per grade increased, the contribution of within-class transmission risk declined and was replaced by within-grade transmission.Our results suggested that interventions such as reducing class sizes or the number of students present (staggered attendance) may not be effective in constrast to what would be expected under the density-dependent mixing assumption(27)(28)(29)(30)(31).…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…The estimated breakdown of RS revealed a number of notable patterns. As the number of classes per grade increased, the contribution of within-class transmission risk declined and was replaced by within-grade transmission.Our results suggested that interventions such as reducing class sizes or the number of students present (staggered attendance) may not be effective in constrast to what would be expected under the density-dependent mixing assumption(27)(28)(29)(30)(31).…”
mentioning
confidence: 73%
“…These makes it challenging to interpret simulation studies evaluating school-based interventions (e.g. reduced class sizes) because the estimated effect sizes can heavily rely on the assumed mixing patterns (27)(28)(29)(30)(31).…”
mentioning
confidence: 99%